Index Assessment of Periodontal Tissue Status in Young Adults with Chronic Catarrhal Gingivitis - Melnyk О.; Batih І. (Actual Dentistry, 2025)
Summary. Periodontal diseases represent a significant issue in modern dentistry, with both medical and social implications. This is due to their high prevalence, the intensity of the disease process, the subsequent formation of chronic odontogenic foci of infection, tooth loss at a young age, and, consequently, a reduced quality of life. Aim: assess the condition of periodontal tissues in young individuals with chronic catarrhal gingivitis, based on the values of the papillary-marginal-alveolar (PMA) index. Material and methods. Two study groups were formed: Group I included 58 patients with chronic gingivitis whose PMA index was less than 30%; Group II consisted of 38 individuals with an inflammatory periodontal process and a PMA index greater than 30%. The following indices were determined: the papillary-marginal-alveolar (PMA) index, the Papillary Bleeding Index (PBI), and the Green-Vermillion Oral Hygiene Index. Results. In Group I, the PMA index was 20.12 ± 2.20%, indicating a mild degree of gingival inflammation. In Group II, the index reached the upper limit of a moderate degree of gingivitis (49.04 ± 4.16%), which was 2.4 times higher than in Group I (p < 0.01). The mean PBI index in Group I was 0.35 ± 0.04, reflecting a low level of gingival papilla bleeding. In Group II, this index was 2.7 times higher, indicating more pronounced gingival bleeding (0.94 ± 0.07, p < 0.01). The Green-Vermillion index in Group I fell within the range indicating satisfactory oral hygiene (1.54 ± 0.16), while in Group II, an unsatisfactory level of oral hygiene was observed (2.47 ± 0.22, p < 0.01). Conclusions. A direct relationship was observed between the papillary-marginal-alveolar index and the severity of periodontal disease in young individuals. Our findings also confirmed existing scientific data on the correlation between oral hygiene levels and the condition of periodontal tissues. An increase in gingival bleeding was observed in parallel with elevated hygienic and papillary-marginal-alveolar index values.